Topical phenytoin dressing versus conventional dressing in diabetic ulcers - Bharadva, Pankaj B.; Choksi, Dilip B.; Damor, Sushil; Shah, Jigar (International Surgery Journal, 2017)
Background: Diabetic foot ulcer is estimated to affect 15% of all diabetic individuals during their lifetime. Management requires a multisystem approach. Various techniques have been tried to treat chronic ulcers, but none was proved to be ideal. Methods: This is a prospective randomised comparative study, where 56 patients with diabetic foot ulcers admitted in dept of surgery SSG hospital, Baroda, india were divided into two comparable groups. Of which 28 underwent topical phenytoin dressings, remaining 28 underwent Betadine dressing (5% w/v povidone – iodine solution). The variables were compared after 14 days based on rate of granulation tissue formation as percentage of ulcer surface area, wound culture-sensitivity and duration of hospital stay. Chi square test was used to compare the data at each of the assessment point in both groups. Results: In Phenytoin group, the mean rate of healthy granulation tissue formation was 60.71%, and mean hospital stay was 23.96 days with negative culture sensitivity was 54%. The Betadine group showed, the mean rate of granulation tissue formation was 11%, and mean hospital stay was 35 days with negative culture sensitivity was 18%. Conclusions: Topical phenytoin dressing considered as superior and cost effective in management of diabetic ulcers.